Evaluation of a digital reporting and supporting tool in breast cancer prevention trials (KarmApp) - José Tapia; Marike Gabrielson; Mattias Hammarström; Yvonne Wengström; Jenny Bergqvist; Aki Tuuliainen; Mikael Eriksson; Kamila Czene; Per Hall; Magnus Bäcklund (BMC Health Services Research)
Abstract Background Anti-estrogens are widely used to reduce recurrence in breast cancer patients. The side effects often lead to treatment non-adherence and the use of anti-hormonal treatments as primary prevention in women with increased risk of breast cancer is very low. We have conducted breast cancer prevention trials aiming to lower the adverse effects of anti-hormones, but with retained effect. For increased two-way communication and to facilitate effective reporting of adverse events we have developed a smartphone application (app), the KarmApp. The aim of our study was to explore the user frequencies of the different features of the app, and if the use is influenced by age and has changed over time. Methods Healthy women aged 40–74, attending the Swedish mammography screening program, were invited to participate in trials evaluating risk-reducing medications at different doses and formulations (KARISMA 2, N = 1,440, KARMA Creme, N = 90, and KARISMA Endoxifen, N = 240). After inclusion, participants were given instructions on how to use the app. We retrospectively evaluated the usage frequencies of the KarmApp and its various functions from 2016 to 2024. To explore the age factor attributed to KarmApp usage, age groups were formed and age was also analyzed as a continuous variable, using logistic regression. Results Of 1,770 participants, 1,646 (93.0%) used the KarmApp and there were 17,065 user interactions, corresponding to 9.6 interactions per person. “Study Activities Overview” was the feature most frequently used. A total of 2,985 adverse events were reported, 2,309 (77.4%) via the KarmApp. The remaining reports were mainly done via phone calls. The younger age, the more likely women were to use the app (p < 0.001), but 75% of women in the highest age group, 60–74 years, used the app. The proportion of users increased over time. Conclusions A vast majority chose to use the KarmApp and reported side effects via the app. More prevalent use was seen among younger participants and use increased over calendar period. Supported by our data, KarmApp exemplifies the potential of using mobile technologies in clinical trials.